Post-Pandemic Learning: : Insights from Indian College Students - Srivastava, Prakhar; Bano, Samina; Abidi, Shuby (Voices of Teachers and Teacher Educators, 2024)
The COVID-19 pandemic compelled educational institutions worldwide to explore online learning. Although it ensured the continuity of education, it brought many challenges, such as sudden transitions, an uncertain future, lack of motivation and reduced social support. Globally, many studies have examined the online learning experiences of students. This study investigates the experiences of Indian college students with online learning during COVID-19 using reflexive thematic analysis. This qualitative study follows a phenomenological epistemology. A total of 12 students (five males and seven females), aged 18–21 years, from a central university in New Delhi, participated in the research. Data were collected through semi-structured interviews and analysed using reflexive thematic analysis. Four overarching themes emerged from the data. i. Feeling disconnected from teachers and peers ii. Experiencing intellectual degradation iii. Lack of exposure to diversity iv. A silver lining—emergence of new possibilities The study captured both positive and negative experiences related to online learning. By incorporating the perspectives of Indian college students, it contributes to the global discussion on online education during Covid-19. The findings can help enhance preparedness for future emergencies and contribute to designing better online education systems by improving digital infrastructure and using technology to facilitate human connections, motivation and engagement